Myeloid Nrf2 Protects against Neonatal Oxidant-Stress-Induced Lung Inflammation and Alveolar Simplification in Mice - Chandra Mohan Tamatam; Lalith Kumar Venkareddy; Aparna Ankireddy; Narsa Machireddy; Sekhart P. Reddy (MDPI AG, 2024)
Bronchopulmonary dysplasia (BPD) is a chronic condition affecting preterm infants, characterized by lung alveolar simplification/hypoalveolarization and vascular remodeling. The nuclear factor erythroid 2 like 2 (Nfe2l2, or Nrf2) plays a critical role in the cytoprotective response to neonatal hyperoxia, and its global deficiency exacerbates hypoalveolarization in mice. The abnormal recruitment and activation of myeloid cells are associated with the pathogenesis of BPD. Therefore, we employed a genetic approach to investigate the role of myeloid Nrf2 in regulating hyperoxia-induced hypoalveolarization. Pups, both wild-type (Nrf2f/f) and those with a myeloid Nrf2 deletion (abbreviated as Nrf2∆/∆mye), were exposed to hyperoxia for 72 h at postnatal day 1 (Pnd1), and then sacrificed at either Pnd4 or Pnd18 following a two-week recovery period. We analyzed the hypoalveolarization, inflammation, and gene expression related to cytoprotective and inflammatory responses in the lungs of these pups. The hypoalveolarization induced by hyperoxia was significantly greater in Nrf2∆/∆mye pups compared to their Nrf2f/f counterparts (35.88% vs. 21.01%, respectively) and was accompanied by increased levels of inflammatory cells and IL-1β activation in the lungs. Antioxidant gene expression in response to neonatal hyperoxia was lower in Nrf2∆/∆mye pups compared to their Nrf2f/f counterparts. Furthermore, Nrf2-deficient macrophages exposed to hyperoxia exhibited markedly decreased cytoprotective gene expression and increased IL-1β levels compared to Nrf2-sufficient cells. Our findings demonstrate the crucial role of myeloid Nrf2 in mitigating hyperoxia-induced lung hypoalveolarization and inflammatory responses in neonatal mice.